ANALISIS KEBIJAKAN PENCEGAHAN DAN PENANGGULANGAN STUNTING DI INDONESIA: Dengan Pendekatan What Is The Problem Represented To Be? - Made Agus Sugianto (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This study analyzes policies on the prevention and control of stunting in Indonesia with the approach "What is the problem represented to be ?". The methodology used is poststructural for policy analysis. This research reveals that issues of commitment and community participation are the main issues that arise in stunting prevention and control policies. In terms of commitment, policies related to budgets and coordination between government institutions to alleviate stunting problems. In addition, stunting prevention policies are more dominated by the government, while the role of the community is still very limited. It is necessary to strengthen regulations to ensure the implementation of efforts to prevent and combat stunting in the regions and requires the involvement of the mass media to increase knowledge and community participation.